Family Impacts on Self-Esteem in Chinese College Freshmen - Shi, Jingyu; Wang, Lu; Yao, Yuhong; Su, Na; Zhao, Xudong; Chen, Fazhan (Frontiers in Psychiatry, 2017)
Abstract This study examined the impact of family function and family-related factors, such as being an only child, grandparenting, income and family relationship on the self-esteem in late adolescencecollege students who are in the transitional period from late adolescence to emerging adulthood. The participants were 2001 Chinese university freshmen with the age from 16 to 20 years. Data were collected by using the Family Assessment Device, the Rosenberg Self-esteem Scale, and Self-report of family information. Comparison analysis indicated that the students from one child families, harmonious families, from families with higher income or raised by their parents without the experience of grandparentinggrandparents raising are more likely to show high self-esteem than their counterparts. Moreover, a multiple regression showed that such dimensions of FAD as Role，Communication，Behavior Control and Problem solving Solving predicted level of self-esteem of the college students, ranging from 13.2% to 17.9% varianceplay important role on self-esteem of the students. The results of this study showed that the self-esteem of the college freshmen is highly correlated with their family’s performance. Therefore, the program focusing on improving family functioning is needed, in order to enhance the self-esteem of the young people and hence contribute to promoting the mental health of them.